Analytical and clinical characterization of a novel high-sensitivity cardiac troponin assay in a United States population - Christenson, Robert H.; Duh, Show-Hong; Mullins, Kristin E.; LeClair, Margot M.; Grigorov, Ilya L.; Peacock, W. Frank (Clinical biochemistry, 2020)
Cardiac troponin (cTn) is the keystone for diagnosis of acute myocardial infarction (AMI). We examined the analytical and clinical diagnostic characteristics of the ACCESS hsTnI assay in a United States (US) population. All measurements and studies were conducted using a lithium heparin matrix. Sex-specific 99th percentile upper reference limits (URLs) were determined for 1089 healthy women (54.6%) and men using non-parametric statistics. High-sensitivity (hs) performance was assessed to determine if the total CV was ≤10% at sex-specific URLs, and if ≥50% of cTnI values for each sex exceeded the assay’s limit of detection (LoD). Precision, analytical measurement range, high-dose hook effect, and endogenous/exogenous interferences were examined with CLSI guidance. Clinical characterization included serial sampling of 1854 suspected AMI subjects presenting to 14 US Emergency Departments. AMI was adjudicated by a panel of expert cardiologists. The study’s only exclusion was end stage renal disease. 99th percentile URLs were 11.6-, 19.8- and 17.5-ng/L for respective female, male and all-subject populations. Total %CV was <8% from 6.8 to 19,000 ng/L, and <6% at sex-specific 99th percentiles; ≥99% of ACCESS hsTnI values for each sex exceeded the LoD. No high-dose hook effect or endogenous/exogenous interferences were identified. A comparison of Baseline samples collected at ≤1 h and any-time after presentation, found 4% lower sensitivity for AMI than with earlier sampling. For 1–9 h post presentation, the sensitivity was >90%, specificity >85%; and negative and positive predictive value were ≥99% and >60%, respectively. Analytical and clinical performance of the ACCESS hsTnI assay meets the definition of a hs cTn method. The ACCESS hsTnI assay has good precision over a wide range, no significant interferences, and sensitivity >90% and NPV ≥99%. Performance is appropriate for aiding in AMI diagnosis.